Macronutrient intake of chronic energy deficiency pregnant women in Pekanbaru city - Dewi Erowati; Dewi Rahayu; Yolahumaroh Yolahumaroh (University of Darussalam Gontor, 2022)
Background: The condition of inadequate energy and macronutrients that causes the inadequate nutritional needs of pregnant women is called Chronic Energy Deficiency (CED). This condition is a risk factor for the incidence of low birth weight babies that can increase the risk of stunting. One of the factors that affect CED is food intake that is not varied and inadequate. Objective: The purpose of the study was to determine the description of the intake of groups of pregnant women who experienced CED and normal (not experienced CED). Method: The type of the research was descriptive research and data collection techniques were carried out using cluster random sampling technique which was carried out at 12 Primary Health Care in Pekanbaru City consisting of 20 CED pregnant women and 20 normal pregnant women. Data was collected by interviewing a questionnaire consisting of the identity of the respondent, economic status and household food security; 2x24 hours recall, and anthropometric measurements of upper arm circumference. Results: Macronutrient intake of pregnant women in Pekanbaru City with chronic energy deficiency (upper arm circumference <23.5 cm) and normal (upper arm circumference ≥ 23.5 cm) was categorized as inadequate the nutritional needs of pregnant women. Conclusion: It is necessary to provide additional food in the form of biscuits with local food ingredients and education by health workers to pregnant women.